Elderly people and online radio: when opposites attract - Rego, Lénia (2016)
This research aims to analyze the relationship between the elderly and radio. Through a participatory action research aims to involve a group of elderly in creating an online radio, to study the impact of this action on the intensification of interpersonal relationships, socialization and entertainment, contributing to active aging. It is also our objective to analyze what is the relationship between the elderly and radio in general, what kind of influence does this have or havehad in their lives and in their daily lives. In a second phase the radio will also be studied, SIM radio we consider that is the national radio that most identify with this age group, particularly in programming, music and advertising that transmits easily identifiable with an aging population.Today's society is more aged. Increased life expectancy and declining birth rate led to an increase in the percentage of elderly in many countries, which requires to be studied and implemented measures to allow for aging well. To advances in medicine join recreational, cultural and educational programs developed at European level todrive the elderly to opt for active aging. Embedded in a speed society, the immediate, new technologies, these seniors are also called to acquire digital skills that facilitate their integration.